1994
DOI: 10.1002/1097-0142(19940901)74:5<1525::aid-cncr2820740506>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Human monoclonal antibodies from stomach carcinoma patients react withhelicobacter pylori and stimulate stomach cancer cells in vitro

Abstract: Background. In recent studies, an increased incidence of gastric adenocarcinomas was observed in patients with Helicobacter pylori infection. However, the extent to which this coincidence is caused by immunologic mechanisms is unknown. Methods. Two human monoclonal antibodies (MoAbs) from patients with stomach carcinoma and H. pylori‐associated gastritis were isolated and established by fusion of spleen cells with the heteromyeloma HAB‐1. The reactivity of these human MoAbs was investigated in functional adhes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 28 publications
0
35
0
Order By: Relevance
“…The fully human monoclonal IgM antibody PAM-1 was isolated from a patient with a stomach carcinoma, too (24). The PAM-1 receptor was found to be a M r 130,000 integral membrane glycoprotein (15), homologous to cysteine-rich fibroblast growth factor receptor 1 (25).…”
Section: Introductionmentioning
confidence: 99%
“…The fully human monoclonal IgM antibody PAM-1 was isolated from a patient with a stomach carcinoma, too (24). The PAM-1 receptor was found to be a M r 130,000 integral membrane glycoprotein (15), homologous to cysteine-rich fibroblast growth factor receptor 1 (25).…”
Section: Introductionmentioning
confidence: 99%
“…As stated in our previous publications (Vollmers et al, 1994;Hensel et al, 1999b), the antibody 103/51 leads to the stimulation of cell line 23132 in vitro. We measured the stimulating ao antibody 103/51 with the mitochondrial hydroxylase assay (MTT), which is a standard assay for proliferation (Carmichael et al, 1987).…”
Section: Stimulation With Human and Murine Monoclonal Antibodiesmentioning
confidence: 99%
“…We have recently shown that stimulating antibodies like the one described here frequently occur in stomach cancer patients, and also that 4 of 11 tumorreactive monoclonal antibodies lead to cell stimulation (Hensel et al, 1999b;Vollmers et al, 1994). Common antigens of the stomach mucosa are the gastric Hϩ/ K(ϩ)-ATPase (Toh et al, 1990) and Lewis blood group antigens .…”
Section: Hensel Et Almentioning
confidence: 99%
See 2 more Smart Citations